Keabsahan Akta Pembagian Hak Waris Yang dibuat oleh Notaris sebagai Dasar Peralihan Hak Atas Tanah - Fauzia, Praninditya Estri (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study aims to identify and analyze the basis of the Notary's authority in making a Deed of Distribution of Inheritance Rights and its validity to be used as the basis for the transfer of land rights due to inheritance. To achieve this objective, an empirical normative legal research was conducted which was descriptive analytical in nature. The data collection method used by the author was a literature study supported by interviews with Notaries. The types of data used were primary data and secondary data with primary, secondary and tertiary legal materials. From the results of the study, it is known that a Notary is an official who is authorized to make a Deed of Distribution of Inheritance Rights based on the authority granted by Article 15 letters (1) and (2) UUJN, and the Deed of Distribution of Inheritance Rights is valid to be used as the basis for the transfer of land rights due to inheritance as regulated in Article 42 paragraph (4) and (5) PP Number 24 of 1997 in conjunction with Article 111 paragraph 5 PMNA/KBN Number 3 of 1997.